Persepsi Korupsi dan Kondisi Makroekonomi Terhadap Investasi Asing Di Indonesia, Filipina dan Thailand - Regina Niken Wilantari; Gelora Seven Saragih; Fajar Wahyu Prianto (Trunojoyo University of Madura, 2020)
Countries in the ASEAN region largely classified as a developing countries. Economic development in developing countries more slowly or lagging from behind developed countries. To catch up, needed enormous capital flows which can not be fulfilled by the flow of capital of domestic. The flow of foreign capital in the form of FDI can be solution in dealing with the limitations of domestic capital. FDI can be potential supporting sector in implementing economic development, besides transferring technologies and skill. The entry of FDI into the country can not be separated from the macroeconomic stability of the country. The purpose of this research was to determine the effect of indicators of fundamental Macroeconomics consisting of economic growth, interest rate, and exchange rate on FDI in five ASEAN countries (Indonesia, Singapore, Malaysia, Thailand, and the Philippines). The research use two analysis method, they are descriptive and quantitative analysis by using Panel Data Regression method which Fixed Effect Model approach. The result of Panel Data Regression which Fixed Effect Model approachshowed that the effect of variables of economic growth and the exchange rate on positive and significant, while the effect of variable interest rate showed on positive significant.